The application of the Project Model Canvas for planning an educational project with remote classes in the period of social distance (Research, Society and Development, 2020)
This article aims to present the Project Model Canvas as a project management methodology that can be applied to the educational field. To carry out this task, a qualitative research was developed, with an exploratory characteristic through bibliographic material on the PMC and its application in the field of education. The example presented was pertinence to today's context, in which the sectors of society, including the educational one, are living, which is the social distancing caused by the COVID-19 pandemic. As a result, an example of the application of the PMC was presented in the elaboration of a Didactic Sequence (DS) for the teaching of Nature Sciences, with the use of remote classes, in the context of social distancing. Thus, at the end of this work, it was possible to conclude that the PMC can be used for the development of educational project, especially in this current context, contributing to the continuity of the school routine.